(3efGQ CUhd GdaJhi hbhGYO GdEaJGA HGdCbhis - (3EHQGgje Hf EHQGgje GddbGfj GdeGdcj,J (B1041 (3g` s ((3eMeO Hf GdeNJGQ Hf MjeO eMeO Hf CMeO Hf eMeO Hf CYeQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi EUWai dMed Ojfg CeG HYO ajbhd hQO Ydi cJGH HNW YGde GdESdGe GdTjN LeGd GdOjf NWjH eOjfI GdbjQhGf aaVVJ Yfg GdNJGe hEPG ai Pjdg GdWhjd eG eMUhdg Ldjd , hgj GdeSCdI GdTgjQI CYfi LYd GdWdGb GdKdGK ai cdeI hGMOIs
(3BNQgG (B:s
(3hbO CTGQ Edi Pdc ai GdMOjK Hbhdg (B: (3MJi JPhbi YSjdJg hjPhb YSjdJc , hdeG PcQ GHf MLQ TQhW GdEMdGd hdfca YfGf Gdbde Yf GdLhdGf aEfi dSJ ef GdaQSGf GfJgi s
(3GfJgi GdeDda ef JCdjagG SfI (B1029 (3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJH HYV YHGQJgG HGdMeQIs
(3fSNI eUMMI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B554s
Keywords: (3CUhd Gdabgs